Los Angeles contingent - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows marchers from Los Angeles at the National March on Washington for Lesbian and Gay Rights. The marchers carry banners or signs that read, ""An idea whose time has come" Los Angeles community equal rights for lesbians & gays, Oct. 14, 1979", "Life, liberty and the pursuit of happi[ness]" and "Los Angele[s] City Colle[ge]".